Quality or equality? The Norwegian experience with medical monopolies - Rasmussen Knut; Bratlid Dag (BMC, 2007)
Abstract Background In order to maintain both quality and efficiency of health services in a small country with a scattered population, Norway established a monopoly system for 38 highly specialized medical services. The geographical distributions of these services, which are provided by one or two university hospitals only, were analysed. Methods The counties of residence for 2 711 patients admitted for the first time in 2001 to these 31 monopolies and 7 duopolies were identified. Results The general tendency observed was that with increasing distance from residential home to monopoly hospitals there was a declining coverage of these health services. The same pattern was found even with regard to explicit diagnoses or treatments such as organ transplantations (except renal transplantations). Duopolies seemed to yield a more even geographical distribution of the services. Conclusion Monopolies may serve as a useful means for maintaining quality in highly specialized medical services, but seem to have an inherent tendency to do this at the expense of geographical equality.